2017
DOI: 10.5694/mja16.00990
|View full text |Cite
|
Sign up to set email alerts
|

Hot water immersionvicepacks for treating the pain ofChironex fleckeristings: a randomised controlled trial

Abstract: Australian New Zealand Clinical Trials Registry, ACTRN12605000007639.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 12 publications
1
8
0
Order By: Relevance
“…Lower limb stings were treated in a bath filled with hot water that had passed through a thermostatic mixing valve set at 45°C. For smaller stings, a bucket was used, which was continually refilled with water from the same tap 2 . We agree that the severity of stings was less than the severity reported in the previous study by Currie and Jacups 3 …”
supporting
confidence: 58%
See 1 more Smart Citation
“…Lower limb stings were treated in a bath filled with hot water that had passed through a thermostatic mixing valve set at 45°C. For smaller stings, a bucket was used, which was continually refilled with water from the same tap 2 . We agree that the severity of stings was less than the severity reported in the previous study by Currie and Jacups 3 …”
supporting
confidence: 58%
“…In our trial, 2 heat or ice were not used before recruiting patients to the study. Lower limb stings were treated in a bath filled with hot water that had passed through a thermostatic mixing valve set at 45°C.…”
mentioning
confidence: 99%
“…In this issue of the MJA , Isbister and colleagues report that hot water immersion was no more effective than ice packs for treating the pain of stings by the box jellyfish ( Chironex fleckeri ) 1 . This finding is surprising, as jellyfish venoms are heat‐labile, 2 but unsurprising, given that heat treatment for some patients did not begin until 4 hours after the patient was stung.…”
mentioning
confidence: 99%
“…I congratulate Isbister and colleagues 1 for performing a first aid randomised controlled trial on box jellyfish stings (a rarity in toxinology). The result is at variance with other studies on this topic (although they mainly involved North American jellyfish stings) 2 …”
mentioning
confidence: 99%
“…The article by Currie and Jacups 5 also reported that 71% of patients received ice. The current trial 1 does not detail if ice (or heat) was applied to patients before enrolling in the study.…”
mentioning
confidence: 99%